2014
DOI: 10.1007/s10549-014-3215-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of circulating tumor cells in metastatic breast cancer

Abstract: Circulating tumor cells (CTCs) are prognostic in all stages of breast cancer. However, since they are extremely rare, little is known about the molecular nature of these cells. We report a novel strategy for the isolation and expression profiling of pure populations of CTCs derived from peripheral blood. We developed a method to isolate CTCs based on immunomagnetic capture followed by fluorescence-activated cell sorting (IE/FACS). After assay validation using the BT474 cell line spiked into blood samples in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 33 publications
3
52
0
Order By: Relevance
“…When coupled to high-throughput microarray or RNAsequencing technologies and unbiased bioinformatics analyses, the aforementioned obstacles are significantly surmounted (Curtis, 2015;Magbanua and Park, 2014). Overall, these new-generation studies have allowed single-cell and bulk-cell analyses of CTCs, which efficiently capture the transcriptional heterogeneity and identify the molecular portraits of metastasizing cells (Ascolani et al, 2015;Cassatella et al, 2012;De Mattos-Arruda et al, 2013;Fina et al, 2015;Lang et al, 2015;Polzer et al, 2014;Powell et al, 2012). For example, one study has demonstrated that CTCs express various biomarkers and mediators of EMT (Yu et al, 2013), a phenotypic change crucial for the completion of the metastatic cascade (Bill and Christofori, 2015;Hanahan and Weinberg, 2011;Kalluri, 2009;Kalluri and Weinberg, 2009;Radaelli et al, 2009).…”
Section: Molecular Profiling Of Circulating Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…When coupled to high-throughput microarray or RNAsequencing technologies and unbiased bioinformatics analyses, the aforementioned obstacles are significantly surmounted (Curtis, 2015;Magbanua and Park, 2014). Overall, these new-generation studies have allowed single-cell and bulk-cell analyses of CTCs, which efficiently capture the transcriptional heterogeneity and identify the molecular portraits of metastasizing cells (Ascolani et al, 2015;Cassatella et al, 2012;De Mattos-Arruda et al, 2013;Fina et al, 2015;Lang et al, 2015;Polzer et al, 2014;Powell et al, 2012). For example, one study has demonstrated that CTCs express various biomarkers and mediators of EMT (Yu et al, 2013), a phenotypic change crucial for the completion of the metastatic cascade (Bill and Christofori, 2015;Hanahan and Weinberg, 2011;Kalluri, 2009;Kalluri and Weinberg, 2009;Radaelli et al, 2009).…”
Section: Molecular Profiling Of Circulating Tumor Cellsmentioning
confidence: 99%
“…with regard to their epidermal growth factor receptor 2 (EGFR2) status. Strikingly, CTC incidence might be observed in the peripheral blood of breast cancer patients, even after removal of the primary tumor, posing additional layers of complexity with regard to the specific origin of these cells and their relationship to dissemination from the primary tumor (Baccelli et al, 2013;Bidard et al, 2014;Curtis, 2015;Lang et al, 2015;Magbanua and Park, 2014;Pukazhendhi and Glück, 2014). As such, molecular signatures derived from CTCs should always be interpreted with caution.…”
Section: Molecular Profiling Of Circulating Tumor Cellsmentioning
confidence: 99%
“…Importantly, they found high transcript levels of genes associated with metastases: NPTN, S100A4, S100A9, and with epithelial mesenchymal transition: VIM, TGFβ1, ZEB2, FOXC1, CXCR4 [103]. More recently, Lang et al published a study of RNA expression profiling of breast cancer CTCs using cDNA microarrays [104]. …”
Section: Methods For Studying Tumour Heterogeneitymentioning
confidence: 99%
“…Robust technologies have been developed to provide genome-wide maps of most epigenetic marks. ChIP-seq, suitable for studying histone marks at the single-cell level, combines chromatin precipitation with next generation sequencing [104]. To assess methylation levels, the most comprehensive picture can be obtained from whole-genome bisulphite sequencing (WGBS) [89], but precipitation techniques (methylated-DNA immunoprecipitation sequencing and methylated–DNA-binding domain sequencing) or reduced-representation bisulphite sequencing (RRBS) [90] are also used.…”
Section: Methods For Studying Tumour Heterogeneitymentioning
confidence: 99%
“…Most DTCs in the bone marrow display properties of epithelial‐mesenchymal transition, during which they gain expression of the mesenchymal marker N‐cadherin and lose expression of the epithelial marker E‐cadherin (Figure ) . The synergistic effect of Snail and β‐catenin confers cancer cells the ability to survive during dissemination and invasion .…”
Section: Characterization Of Ctcs and Dtcs In Bone Marrowmentioning
confidence: 99%